Implementation of coaching methods to decrease the parenting stress levels among teenage mothers in Indonesia: A quasi-experimental study - Saleh, Ariyanti; Irwan, Andi Masyitha; Latif, Aulia Insani; Syahrul, Syahrul; Hadju, Veni; Andriani, Irma; Restika, Indah (Belitung Nursing Journal, 2024)
Background: The high rate of early marriage, teenage pregnancy, and teenage mothers increases the prevalence of emotional and mental disorders, depression, parenting stress, and child stunting. Parenting coaching is among the effective ways to overcome parenting stress and improve parents’ knowledge, skills, and behaviors, thereby avoiding child stunting. However, studies on parenting coaching are not widely conducted, particularly in Indonesia. Objective: This study aimed to present the current status of parenting stress among teenage mothers and assess whether parenting coaching effectively reduces parenting stress among teenage mothers. Methods: A quasi-experimental design was used. The participants were randomly selected into two groups: the intervention group receiving parenting coaching intervention and the control group receiving standard education using a leaflet. Data were collected in June 2021 in Takalar Regency, South Sulawesi, Indonesia. Statistical Program for Social Science version 21 (Armonk, NY, USA) was employed for all statistical analyses. Results: The parenting coaching intervention had a significant effect on parenting stress (p <0.001), with significant positive changes in knowledge, attitude (p <0.001), behavior (p <0.001), self-efficacy (p <0.001), and maternal function (p <0.001). Additionally, a significant difference in the achievement of z-score values was observed between the intervention and control groups based on Body Weight/Age (BW/A) (p <0.001) and Body Length/Age (BL/A) (p <0.001). However, Body Weight/Body Length (BW/BL) did not show a significant difference in the achievement of z-score (p = 0.34) in the third month. Conclusion: Parenting coaching can reduce parenting stress among teenage mothers and improve their knowledge, attitudes, behavior, self-efficacy, and maternal function; hence, this intervention can be used as a reference in the nursing process to reduce parenting stress and prevent child stunting.